Injury patterns in Swedish elite athletics: annual incidence, injury types and risk factors - Jacobsson, J.; Timpka, T.; Kowalski, J.; Nilsson, S.; Ekberg, J.; Dahlström, Ö.; Renström, P. A. (British Journal of Sports Medicine, 2013)
Objective To estimate the incidence, type and severity of musculoskeletal injuries in youth and adult elite athletics athletes and to explore risk factors for sustaining injuries. Design Prospective cohort study conducted during a 52-week period. Setting Male and female youth and adult athletics athletes ranked in the top 10 in Sweden (n=292). Results 199 (68%) athletes reported an injury during the study season. Ninety-six per cent of the reported injuries were non-traumatic (associated with overuse). Most injuries (51%) were severe, causing a period of absence from normal training exceeding 3 weeks. Logrank tests revealed risk differences with regard to athlete category (p=0.046), recent previous injury (>3 weeks time-loss; p=0.039) and training load rank index (TLRI; p=0.019). Cox proportional hazards regression analyses showed that athletes in the third (HR 1.79; 95% CI 1.54 to 2.78) and fourth TLRI quartiles (HR 1.79; 95% CI 1.16 to 2.74) had almost a twofold increased risk of injury compared with their peers in the first quartile and interaction effects between athlete category and previous injury; youth male athletes with a previous serious injury had more than a fourfold increased risk of injury (HR=4.39; 95% CI 2.20 to 8.77) compared with youth females with no previous injury. Conclusions The injury incidence among both youth and adult elite athletics athletes is high. A training load index combing hours and intensity and a history of severe injury the previous year were predictors for injury. Further studies on measures to quantify training content and protocols for safe return to athletics are warranted.